Biocatalyzed synthesis of flavor esters and polyesters: A design of experiments (DoE) approach - Fabbri F.; Bertolini F. A.; Guebitz G. M.; Pellis A. (International Journal of Molecular Sciences, 2021)
In the present work, different hydrolases were adsorbed onto polypropylene beads to investigate their activity both in short‐esters and polyesters synthesis. The software MODDE® Pro 13 (Sartorius) was used to develop a full‐factorial design of experiments (DoE) to analyse the thermostability and selectivity of the immobilized enzyme towards alcohols and acids with different chain lengths in short‐esters synthesis reactions. The temperature optima of Candida antarctica lipase B (CaLB), Humicola insolens cutinase (HiC), and Thermobifida cellulosilytica cutinase 1 (Thc_Cut1) were 85 °C, 70 °C, and 50 °C. CaLB and HiC preferred long‐chain alcohols and acids as substrate in contrast to Thc_Cut1, which was more active on short‐chain monomers. Polymerization of different esters as building blocks was carried out to confirm the applicability of the obtained model on larger macromolecules. The selectivity of both CaLB and HiC was investigated and best results were obtained for dimethyl sebacate (DMSe), leading to polyesters with a Mw of 18 kDa and 6 kDa. For the polymerization of dimethyl adipate (DMA) with BDO and ODO, higher molecular masses were obtained when using CaLB onto polypropylene beads (CaLB_PP) as compared with CaLB immobilized on macroporous acrylic resin beads (i.e., Novozym 435). Namely, for BDO the Mn were 7500 and 4300 Da and for ODO 8100 and 5000 Da for CaLB_PP and for the commercial enzymes, respectively. Thc_Cut1 led to polymers with lower molecular masses, with Mn < 1 kDa. This enzyme showed a temperature optimum of 50 °C with 63% of DMA and BDO when compared to 54% and 27%, at 70 °C and at 85 °C, respectively.